Retelling Local Legends: Implementing CIRC In Teaching Writing Narrative Text - Bella Maidiya Putri; sayid wijaya (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2019)
Abstract: Introducing local legends is crucial for students to preserve their existence. However,  many students in SMAN 1 Katibung South Lampung found it difficult to retell narrative text in writing, especially local legends, because they are lack of grammar and vocabulary and they found it difficult to develop and to express their ideas in making narrative text writing. Therefore, the research applied Cooperative Integrated Reading and Composition (CIRC) technique as an effective technique to students which allowed them to work cooperatively with their friends in a group. The research methodology was quasi experimental design, pretest-posttest design. The population of this research was the eleventh grade of SMAN 1 Katibung South Lampung. Two classes consisting of 30 students for experimental class and 28 students for control class were taken as the sample. In collecting the data of pretest and posttest, writing test was used. The data were analyzed by using SPSS to calculate Independent Simple t-test. From the data analysis, it was found that the result of t-test was Sig. (pvalue) = 0.000 < α = 0.05. Therefore, Ha is accepted which meant that there was influence of using CIRC technique towards students’ writing ability. Keywords: Cooperative Integrated Reading and Composition (CIRC), students’ writing ability, local legends, quasi experimental research